2019
DOI: 10.24200/amecj.v2.i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized graphene-trimethoxyphenyl silane for toluene removal from workplace air by sorbent gas extraction method

Abstract: A new synthesized sorbent based on functionalizing graphene with N-Phenyl-3-aminopropyl trimethoxy silane (G-PhAPTMS, C12H21NO3Si), was developed as a novel sorbent for removal of toluene from air by sorbent gas extraction procedure (SGEP). By proposed method, the removal efficiency of G-PhAPTMS was compared with other sorbents such as activated carbon (AC), graphene (G) and graphene oxide (GO). The standard gas of toluene generated in pure air with different concentrations and the effects of parameters such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The different features for VOCs' removal such as recovery (%), absorption capacity (AC), and aromatic compounds are compared together. Based on the results, the ST/HS-SPE procedure was comparable to other sorbent which was reported in different works (Bagheri Hosseinabadi et al 2019;Osanloo and Qurban-Dadras 2014;Faghihi Zarandi et al 2018;Jahangiri et al 2011;Hansmeier, 2010;Bina et al 2012;Shariq Vohra 2015;Qi et al 2018;Gholami et al 2014;Liu et al 2016;Rostami and Jonidi Jafari 2014;Vahdat Parast et al 2014;Britt et al Table 1 Validation…”
Section: Discussion and Comparing To Other Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…The different features for VOCs' removal such as recovery (%), absorption capacity (AC), and aromatic compounds are compared together. Based on the results, the ST/HS-SPE procedure was comparable to other sorbent which was reported in different works (Bagheri Hosseinabadi et al 2019;Osanloo and Qurban-Dadras 2014;Faghihi Zarandi et al 2018;Jahangiri et al 2011;Hansmeier, 2010;Bina et al 2012;Shariq Vohra 2015;Qi et al 2018;Gholami et al 2014;Liu et al 2016;Rostami and Jonidi Jafari 2014;Vahdat Parast et al 2014;Britt et al Table 1 Validation…”
Section: Discussion and Comparing To Other Methodssupporting
confidence: 74%
“…Also, the leukemia can be seen in human exposure to benzene (Smaelnejad et al 2015). Due to benzene toxicity in human health, some of variable methods including adsorption (Smaelnejad et al 2015;Lashaki et al 2016;Gomez et al 2016;Gou and Bahrami Yarahmadi 2019;Ncube et al 2017;Jamshidzadeh and Shirkhanloo 2019;Bagheri Hosseinabadi et al 2019), photo-catalytic oxidation (Palau et al 2012;Weon and Choi 2016;Boulamanti and Philippopoulos 2008;Shang et al 2002), thermal oxidation and bio filtration (Wong et al 2015;Mohamed et al 2016) were used for removal of VOC's or BTEX from air. Among them, the adsorption process based on carbon sorbents (CNTs, NG, NGO) was used to remove VOCs from air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Shahi Ahangar showed that the photocatalytic removal efficiency in the concentrations of 50, 100, and 300 ppm was equal to 87.8%, 98.9%, and 90.8%, respectively [10]. Many researchers used different pilot and nanoadsorbents (Ni-MWCNTs, GQDs, NGO, NG, MSN, ILs, Silica) to remove hazardous pollutants such as toluene, ethyl benzene, mercury, benzene, dust, and hydrogen sulfide from the air [4,[11][12][13][14][15][16][17][18][19][20]. Finally, according to those mentioned above and the high efficiency of nanoadsorbents compared to other adsorbents in the removal of different materials in the previous studies, a comparison study for adsorption of xylene from the air between commercial activated carbon absorbent and Nano carbon adsorbent was obtained to survey the effect of nanoadsorbent in the removal of xylene from the air.…”
Section: Introductionmentioning
confidence: 99%
“…In other hands, the lead absorb by gastrointestinal of children up to 50% [3]. The aerosols, metals and VOCs were studied in several fields, including epidemiology, respiratory medicine, air purification technology, and air pollution removal by different techniques and pilots [11][12][13][14]. Aerosols are further categorized on the basis of the variation in the particle size.…”
Section: Introductionmentioning
confidence: 99%